THE RELATIONSHIP BETWEEN OBESITY IN CHILDREN AGES 9 - 12 YEARS AND PATTERN OF PLAYING ACTIVITIES - Tanaya, Putu Denny; D.Rianti, Emillia Devi (Universitas Wijaya Kusuma Surabaya, 2015)
Obesity is excess weight as a result of stockpiling body fat excessive and could happen to all citizen including on children. The cause of obesity that one of them caused by the imbalance between intake of nutrients with physical activity that is playing. Good physical activity, the body metabolic processes will make the children walk with a maximum intake of calories that can be obtained from food directly in use in both by the body.Â The aim of this research is to determine the relationship between the obese on 9 to 12 years old kids are playing with a pattern. From the graph is used for children and teenager to define obesity using the Center for Disease Control and Prevention (CDC). Method used by persentil graph body mass index (bmi to age 2 to 20 years in the male and female). Analytic research is the correlation with spearman. The result of research shows that there is no correlation between obesity with a pattern of the activity of playing on children aged 9 to 12 years. Because the value of a correlation coefficient (0.053 > 0.025). It is also avidenced by the result of a coefficient that marked negative and having meaning the absence of correlation ( - 0.209 ). Of the result we can conclude that there are a lot of the main factor in addition to the activity of playing that can cause a child suffering from obesity including genetic factor, and the pattern of hormonal feeding on such a child.